Integrating Islamic Worldview for Sustainable Identity in Science Textbooks in Indonesia - Subagiya, Bahrum; Sauri, Sofyan; Handrianto, Budi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia has a majority Muslim population and has challenges maintaining and strengthening Islamic identity and values in globalization and Western cultural influences. Western influences enter the education sector, especially science education, primarily through textbooks. Science textbooks in Indonesia are often based on Western science paradigms rooted in a naturalistic or materialistic worldview, which contradicts the Islamic worldview. This article explores the Islamic worldview in Basic Natural Science textbooks to strengthen the identity and sustainability of Islamic values in Indonesia. Incorporating the Islamic worldview in science education can provide a holistic and integrated approach to learning, aligning scientific knowledge with Islamic teachings and principles. Although not comprehensive, the Islamic worldview is present in Indonesia's Basic Natural Science textbooks. Steps to strengthen Islamic identity and values in science learning are carried out by Emphasis on understanding the creation of the universe by Allah, integration of moral and ethical values in the context of science, introduction to the contributions of Muslim scientists in the history of science, explaining natural phenomena in the perspective of the Islamic worldview, and correcting science concepts that are not following the Islamic worldview.